2019
DOI: 10.1002/jcpy.1109
|View full text |Cite
|
Sign up to set email alerts
|

Good Guys Can Finish First: How Brand Reputation Affects Extension Evaluations

Abstract: This research investigates how consumer evaluations of brand extensions are affected by two distinct types of brand reputation: a reputation for social responsibility built through commitments to societal obligations, versus a reputation for ability developed by delivering quality offerings. Through six studies, we establish that while the two reputation types equivalently influence high fit brand extensions, a reputation for social responsibility (vs. ability) leads to more favorable responses toward low fit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 91 publications
0
36
0
1
Order By: Relevance
“…Our findings contribute to a better understanding of brand extension evaluations by showing that life-role transition, a seemingly unrelated life event that consumers undergo when evaluating a brand extension, plays a critical role in determining responses toward distant brand extensions. In so doing, our research contributes to an emerging body of research that calls for a better understanding of how consumers evaluate brand extensions, especially distant brand extensions, in realistic marketplace conditions (Cutright, Bettman, and Fitzsimons 2013;Johnson et al 2019;Klink and Smith 2001;Meyvis, Goldsmith, and Dhar 2012;Parker et al 2018), and it reveals that consumers' product preferences can be grounded in their life dynamics. Last, our findings provide practical suggestions for brand managers.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Our findings contribute to a better understanding of brand extension evaluations by showing that life-role transition, a seemingly unrelated life event that consumers undergo when evaluating a brand extension, plays a critical role in determining responses toward distant brand extensions. In so doing, our research contributes to an emerging body of research that calls for a better understanding of how consumers evaluate brand extensions, especially distant brand extensions, in realistic marketplace conditions (Cutright, Bettman, and Fitzsimons 2013;Johnson et al 2019;Klink and Smith 2001;Meyvis, Goldsmith, and Dhar 2012;Parker et al 2018), and it reveals that consumers' product preferences can be grounded in their life dynamics. Last, our findings provide practical suggestions for brand managers.…”
mentioning
confidence: 82%
“…It reinforces the proposition that, in addition to parent brand characteristics (e.g., high vs. low company competence), an understanding of consumer characteristics (i.e., dynamics of their life stage) is critical for determining how consumers react to brand extensions. Although recent research has focused on determinants of responses to distant brand extensions (Cutright, Bettman, and Fitzsimons 2013;Johnson et al 2019;Meyvis, Goldsmith, and Dhar 2012;Parker et al 2018), the current research differs from them and contributes by identifying new mechanisms influencing brand extension evaluation. For example, it differs from Cutright, Bettman, and Fitzsimons (2013), who show that perceived control decreases evaluation for distant brand extensions, in that our operationalization of life-role transition did not affect perceived control.…”
Section: Conceptual Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of consumers, several researchers argue that a brand with strong ability will be more attractive than socially responsible ( Johnson et al, 2017 ), whereas other researchers consider that consumers prefer brands with good socially responsible reputations ( Hur et al, 2013 ). Moreover, a recent study by adopting a behavioral measurement has proved the essential role of the two types of brand reputation effect on brand extension ( Johnson et al, 2019 ). They have indicated that the socially responsible reputation of a brand could provide a warm feeling for consumers and further effectively increase the acceptance of distant extension products.…”
Section: Introductionmentioning
confidence: 99%
“…Debido a ello, existen estudios que pretenden conocer en mayor profundidad cuál es la relación que se genera entre las marcas y las emociones de los consumidores (Tellis et al, 2019;Xie, Bagozzi, & Grønhaug, 2019). Si a pesar de las dificultades que estamos comentando, la compañía consigue crear y transmitir adecuadamente su imagen de marca, y consigue además que esta se mantenga en niveles positivos a lo largo del tiempo, consolidará esa imagen de marca, creando lo que conocemos como reputación (Johnson et al, 2019;Loureiro, Sarmento, & Le-Bellego, 2017). El rendimiento y dicha reputación, se formarán a partir de elementos como el logo, el nombre, la marca en general, así como la conciencia de los usuarios sobre ella (Foroudi, 2019) y supondrá un elemento diferencial en la alta competencia entre marcas que hay en el mercado, mejorando el valor de los productos que ofrece la marca y los resultados económicos de la empresa (Villafañe, 2001).…”
Section: Identidad De Marca E Imagen De Marcaunclassified